The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.mad.2006.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Improving cell therapy—experiments using transplanted telomerase-immortalized cells in immunodeficient mice

Abstract: Cell therapy is the use of stem cells and other types of cells in various therapies for age-related diseases. Two issues that must be addressed before cell therapy could be used routinely in medicine are improved efficacy of the transplanted cells and demonstrated long-term safety. Desirable genetic modifications that could be made to cells to be used for cell therapy include immortalization with hTERT (human telomerase reverse transcriptase). We have used a model for cell therapy in which transplantation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…With respect to the first mechanism, several genes have been evaluated for their potential utility in immortalizing stem cells for use as delivery vehicles: the proto-oncogene v-myc, 3,70,72,[89][90][91] the catalytic component of the telomerase complex (human telomerase reverse transcriptase (hTERT)), human papillomavirus type 16 E6/E7 genes, Bmi-1 [92][93][94][95][96][97][98][99] and an N-terminal fragment of SV40 large T-antigen. 2,100 Characteristics of the resultant cell lines, each of which had extended life spans in culture, have been reviewed.…”
Section: Toxicity/tumorigenicitymentioning
confidence: 99%
“…With respect to the first mechanism, several genes have been evaluated for their potential utility in immortalizing stem cells for use as delivery vehicles: the proto-oncogene v-myc, 3,70,72,[89][90][91] the catalytic component of the telomerase complex (human telomerase reverse transcriptase (hTERT)), human papillomavirus type 16 E6/E7 genes, Bmi-1 [92][93][94][95][96][97][98][99] and an N-terminal fragment of SV40 large T-antigen. 2,100 Characteristics of the resultant cell lines, each of which had extended life spans in culture, have been reviewed.…”
Section: Toxicity/tumorigenicitymentioning
confidence: 99%
“…In our recent studies in the ovarian tissue, we have found that estrogen regulates telomerase activity in the granulosa cells of ovarian follicles (manuscript submitted). Given that transplantation of adrenocortical cells expressing telomerase activity restores the adrenal hormone levels in adrenalectomized mice [36], it is likely that the adrenal gland preserves a population of telomerase-positive cells to retain cell proliferation capacity with differentiation for adequate function of the adrenal gland in mice. Consistent with the hypothesis that estrogen regulates telomerase activity and thereby tissue genesis and repair in a tissue-specific manner, elimination of estrogen causes a significant decrease of telomerase activity in association with the loss of tissue weight of the adrenal gland.…”
Section: Discussionmentioning
confidence: 99%
“…[119][120][121][122] Similarly, ectopic expression of the catalytic domain of human telomerase reverse transcriptase has been evaluated as a strategy to limit proliferative senescence in primary cell populations. 123,124 Despite their potential for enhancing therapeutic cell survival and proliferation, many of these gene products are also associated with malignant transformation. Therefore, nonconstitutive or pharmacologically regulated expression strategies may be required to ensure safety.…”
Section: Localized Survival and Proliferation Improves Targetingmentioning
confidence: 99%